The Relation between Environmental Awareness, Sustainability and Conscious Living among Consumers - Garai-Fodor, Monika; Huszak, Nikolett (Transformations In Business & Economics, 2026)
The research analysed the relationship between sustainable, environmentally conscious behaviour and conscious living. We were interested in the extent to which self-awareness and self-development are crucial dimensions of social and environmental awareness. In case of our quantitative research, snowball sampling method with seeds was used, resulting in 2033 reachable questionnaires. Based on the results, it was found that environmentally conscious, sustainability-seeking consumer attitudes function as a segmentation criterion, three distinct consumer segments could be characterised: ‘conscious, sustainability-seeking consumers’, ‘hesitant consumers’ and ‘risk-aware, empowered consumers’. For all three groups of consumers, we found a statistically significant relationship between the perception of the importance of self-awareness and self-development, which clearly indicated the extent to which these competences play a decisive role in the development of conscious and sustainability-seeking behaviour. The study made concrete suggestions for the adequate development of self-development and self-awareness in relation to enhancing environmentally conscious and sustainable consumer behaviour.
Keywords: sustainability; awareness; self-development